2020
DOI: 10.1111/tmi.13372
|View full text |Cite
|
Sign up to set email alerts
|

Can combined online and face‐to‐face continuing medical education improve the clinical knowledge and skills of family doctors in Vietnam? A cluster randomised controlled trial

Abstract: objectives To assess the effectiveness of a combined online and face-to-face continuing medical education (CME) programme, for improvement in clinical knowledge and skills of family doctors, in comparison with a control group; and to explore the self-reported satisfaction, competencies and confidence of those in the intervention group.methods We used a cluster randomised controlled trial, with pre-and post-testing, and a feedback survey at the end of the 18-month CME programme. The measurements consisted of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Maintaining a portfolio/ e-portfolios -Typically for assessment and involving learners logging their experiences at the most elementary level, but with room to include elements of personal reflection about those experiences at a higher level (Haines et al, 2013) -Negative sentiment towards portfolios among learners -Acceptable if are tied to recertification, revalidation, careerlong updating and CME credit (Haines et al, 2013) ix. Meetings/symposia/seminars -Traditional CME offering (Thai et al, 2020) -May have combination of a didactic lecture, a case discussion and incorporate frequent question and answer sessions (Drexel et al, 2011) -Widespread familiarity with method making it preferable -May not be as effective as other methods (Drexel et al, 2011) x. Mentoring -Can be an adjunct to distance CME.…”
Section: Content Delivery (Choice Of Format)mentioning
confidence: 99%
“…Maintaining a portfolio/ e-portfolios -Typically for assessment and involving learners logging their experiences at the most elementary level, but with room to include elements of personal reflection about those experiences at a higher level (Haines et al, 2013) -Negative sentiment towards portfolios among learners -Acceptable if are tied to recertification, revalidation, careerlong updating and CME credit (Haines et al, 2013) ix. Meetings/symposia/seminars -Traditional CME offering (Thai et al, 2020) -May have combination of a didactic lecture, a case discussion and incorporate frequent question and answer sessions (Drexel et al, 2011) -Widespread familiarity with method making it preferable -May not be as effective as other methods (Drexel et al, 2011) x. Mentoring -Can be an adjunct to distance CME.…”
Section: Content Delivery (Choice Of Format)mentioning
confidence: 99%
“…19 With the continuous enrichment of educational informatization means, the use of online teaching platform to carry out personal self-study has become the first choice for many medical workers. 20 Chinese medical workers are affected by occupational environment, stress, responsibility and other social factors, 11 with a full load or even overload work, resulting in difficulty for full-time study. The results of our survey showed that the favorite training form and way for obtaining resources among doctors with different working years was online, and only 4.70% chose the form of on-site conference presentations.…”
mentioning
confidence: 99%